2009
DOI: 10.1177/875687050902800402
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Differences between Big City and Small Town Special Education Services for Students with Low Incidence Disabilities in Kentucky

Abstract: Researchers have suggested that educational programming for students with low incidence disabilities in rural settings may be limited. In the current study, researchers surveyed special education teachers across Kentucky and collected demographic data on two exemplar districts. Results indicated that differences existed between urban and rural districts on several variables but that some rural communities in Kentucky were able to overcome barriers to the provision of educational programming for students with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
0
19
1
Order By: Relevance
“…This finding is inconsistent with previous studies that suggested that families in rural areas encounter specific difficulties in their search for services (Chen et al 2008;Hutton and Caron 2005;Kohler 1999;Mandell et al 2005;Pennington et al 2009). The population-based approach used in Québec to promote an equitable provision of services among all families living within a catchment area may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…This finding is inconsistent with previous studies that suggested that families in rural areas encounter specific difficulties in their search for services (Chen et al 2008;Hutton and Caron 2005;Kohler 1999;Mandell et al 2005;Pennington et al 2009). The population-based approach used in Québec to promote an equitable provision of services among all families living within a catchment area may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 98%
“…For instance, a child residing in a rural community may obtain a diagnosis 5 months later than one of his or her peers living in an urban community (Mandell et al 2005). This disparity may be due to several factors: a lack of sufficiently trained professionals in rural areas (Hutton and Caron 2005;Kohler 1999;Pennington et al 2009); greater distances between families and service providers (Hutton and Caron 2005;Kohler 1999); a lack of resources (Hutton and Caron 2005); and exceptionally long waiting times in these areas (Hutton and Caron 2005;Mandell et al 2005). Rural families often work with several service providers, take on a substantial portion of the administrative burden, and receive piecemeal and uncoordinated services (Hutton and Caron 2005;Kohler 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The condition can persist for life, with major implications for the individual, the family, and the healthcare system [ 5 ]. There are currently limited medical treatments for individuals with ASD [ 6 ], and while there are several behavioral therapies available for treatment, these programs are inaccessible to many [ 7 , 8 ], are often costly [ 5 , 9 ], are typically less effective as patients age [ 10 ], are not reliably effective [ 11 ], and may address a narrow range of symptoms [ 12 15 ]. A treatment that successfully addresses the limitations of current therapies therefore would be of great value.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, compared with students with other disabilities, children with ASD diagnoses are more than four times as likely to utilize school-based services (Mandell, Walrath, Manteuffel, Sgro, & Pinto-Martin, 2005). However, as with other geographically related findings, children living in rural areas have less access to highly trained special education service providers than children with ASD living in urban areas (Pennington, Horn, & Berrong, 2009). With regard to regional differences, a national survey of parents of children with ASD indicated that ABA therapy was the among the most frequently used services in educational treatments (Green et al, 2006) whereas a state-specific study indicated that a different form of intensive, integrated therapy (i.e., Treatment and Education of Autistic and Related Communication Handicapped Children [TEACCH]) was more commonly utilized than ABA (Thomas et al, 2007).…”
Section: Treatment Selection May Vary By Regionmentioning
confidence: 89%